2012
DOI: 10.1016/j.joca.2011.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-1 boosts the developing process of condylar hyperplasia by stimulating chondrocytes proliferation

Abstract: IGF-1 promotes human TMJ cartilage overgrowth in the developing process of CH by enhancing chondrocytes proliferation via MAPK-ERK pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…The presence of IGF-1 was found mainly in the proliferative and hypertrophic chondrocyte layer, vice versa only a few in the calcified chondrocyte layer. There was the correlation of IGF-1 gene with age and cartilaginous thickness [4,11,18]. The study of SNPs can help to discover the multifactorial etiologies which interaction among of genetic factors with hormonal, neurological, biochemical, and biomechanical [1,8,10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of IGF-1 was found mainly in the proliferative and hypertrophic chondrocyte layer, vice versa only a few in the calcified chondrocyte layer. There was the correlation of IGF-1 gene with age and cartilaginous thickness [4,11,18]. The study of SNPs can help to discover the multifactorial etiologies which interaction among of genetic factors with hormonal, neurological, biochemical, and biomechanical [1,8,10].…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 gene expression depends on to the etiology of mandibular growth in Class III malocclusion [9,10]. IGF-1 promotes human TMJ cartilage overgrowth in the developing process of condylar hyperplasia by enhancing chondrocytes proliferation through MAPK (Mitogen-activated protein kinase)-eERK pathway [11]. Distribution of IGF-1 in condylar hyperplasia patients has been a complicated expression of facial asymmetry in postnatal growth abnormality of the mandibular condyle [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IGF-1 plays an important role in cell proliferation; it is mainly expressed in the liver although also in brain, heart, lung, bone, placenta, and testes and also produced by chondrocytes [72] thus having an autocrine and/or paracrine regulation [73].…”
Section: Insulin-like Growth Factormentioning
confidence: 99%
“…A study by Fu confirmed that cyclic mechanical stretch-enhanced myoblast proliferation was dependent on activated IGF-1R [7]. IGF-1R has been shown to play a vital role in the modulation of chondrocyte activity and functions following chemical stimuli [8]. However, it is presently obscure whether IGF-1R is involved in modulating mechanical stress-initiated mitogenic effects in chondrocytes.…”
Section: Introductionmentioning
confidence: 98%